2015
DOI: 10.1007/s11892-015-0629-y
|View full text |Cite
|
Sign up to set email alerts
|

Salt Restriction in Diabetes

Abstract: There are no long-term interventions examining the effects of salt reduction in people with diabetes, and these are urgently required. Sodium reduction is controversial as it appears that an intake below 2.5 g and above 6 g/day of salt is associated with increased cardiovascular disease risk. However, pre-existing illness leading to a lower salt intake may confound the findings. Only a few studies have prospectively collected data on the sodium intake and excretion of people with diabetes and examined hard end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Persons with prevalent diabetes knew their diabetes status and had encountered physicians or other health professionals with regards to the management of their condition; as part of the management of diabetes condition, patients are counseled to avoid lifestyles that will predispose them to cardiovascular diseases and limiting salt intake is one of the key management strategies of hypertension and subsequent cardiovascular diseases ( 27 ). In a prospective study of dietary salt intake and diabetes, salt was found to be associated with incident diabetes ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Persons with prevalent diabetes knew their diabetes status and had encountered physicians or other health professionals with regards to the management of their condition; as part of the management of diabetes condition, patients are counseled to avoid lifestyles that will predispose them to cardiovascular diseases and limiting salt intake is one of the key management strategies of hypertension and subsequent cardiovascular diseases ( 27 ). In a prospective study of dietary salt intake and diabetes, salt was found to be associated with incident diabetes ( 28 ).…”
Section: Discussionmentioning
confidence: 99%